(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The educational process is extremely complex. The effectiveness of education depends on the activity of both the teacher and the student, the availability of teaching tools, the organizational, scientific, and methodological perfection of the educational process, the society’s need for knowledgeable individuals, and other yet-to-be-identified factors. Society demands high educational effectiveness based on its social-political needs. Currently, as economic structures based on market relations are being established in Uzbekistan, there is a growing demand for individuals who have broad and deep knowledge and can apply it practically. Knowledgeable, entrepreneurial, and socially active individuals find their place in society and work.